Oral History Collections at Research University Libraries in Malaysia - Mohamad, Radia Banu Jan; Jaafar, Cik Ramlah Che; Saad, Siti Roudhah Mohamad; Misaridin, Shahriza Fadly (2012)
Oral history has usually meant as an account of historical event, person or place, a first person memory of the past, by an eyewitness. It is considered as living memories which have great importance in the history of mankind. It has also become a key resource for reconstructing, recreating and recording past and present knowledge of society. Academic libraries have served as repositories for books and manuscripts that help in revealing the stories of world’s civilization for centuries. These civilizations have secured their history by training particular individuals to remember, to record and to pass the updated tradition on to the next generation orally. Sadly, much of our pasts, in terms of oral history, have not been preserved in academic libraries. Even though Malaysia was among the first country in Southeast Asia which have started oral history program in 1960s, activities on oral history conducted or collected by academic libraries in Malaysia appear to be vague. Over the years, various factors in library management have affected oral history activities and program and has brought it to a standstill.